Dermal αSMA+ myofibroblasts orchestrate skin wound repair via β1 integrin and independent of type I collagen production. (25th February 2022) - McAndrews, Kathleen M; Miyake, Toru; Ehsanipour, Ehsan A; Kelly, Patience J; Becker, Lisa M; McGrail, Daniel J; Sugimoto, Hikaru; LeBleu, Valerie S; Ge, Yejing; Kalluri, Raghu
Abstract: Skin wound repair is essential for organismal survival and failure of which leads to non‐healing wounds, a leading health issue worldwide. However, mechanistic understanding of chronic wounds remains a major challenge due to lack of appropriate genetic mouse models. αSMA + myofibroblasts, a unique class of dermal fibroblasts, are associated with cutaneous wound healing but their precise function remains unknown. We demonstrate that genetic depletion of αSMA + myofibroblasts leads to pleiotropic wound healing defects, including lack of reepithelialization and granulation, dampened angiogenesis, and heightened hypoxia, hallmarks of chronic non‐healing wounds. Other wound‐associated FAP + and FSP1 + fibroblasts do not exhibit such dominant functions. While type I collagen (COL1) expressing cells play a role in the repair process, COL1 produced by αSMA + myofibroblasts is surprisingly dispensable for wound repair. In contrast, we show that β1 integrin from αSMA + myofibroblasts, but not TGFβRII, is essential for wound healing, facilitating contractility, reepithelization, and vascularization. Collectively, our study provides evidence for the functions of myofibroblasts in β1 integrin‐mediated wound repair with potential implications for treating chronic non‐healing wounds. Synopsis: Among the heterogeneous population of tissue fibroblasts, the exact role of dermal αSMA + myofibroblasts and their functional mediators remain poorly resolved. Here, extensive genetics combined with single‐cell profiling uncover aSMA + myofibroblasts as essential contributors to cutaneous wound healing, offering potential treatment strategies. Depletion of αSMA + myofibroblasts in mice leads to chronic non‐healing wounds. Type I collagen and TGFβRII from αSMA + myofibroblasts are dispensable for wound healing. β1 integrin facilitates αSMA + myofibroblasts‐mediated contractility, reepithelization, and vascularization to promote wound repair. Abstract : Cutaneous chronic wound healing in the mouse requires contribution of aSMA + dermal myofibroblasts.